GEOPHYSICS OF PEDOSPHERE AND ENVIRONMENTAL STUDIES OF V.I. VERNADSKY - Menshov, O.; Sukhorada, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The scientific achievements of V.I. Vernadsky and V.V. Dokuchaev for soil science are considered. The foundations of the geophysics of pedosphere concept are given. The possibilities of magnetic investigations of soils are shown.